Theory and Experiment Research of Transmission Efficiency of Split-power Internal Parallel Moving Gear Transmission - Zhao Ziqiang; Yin Xuebin; Wang Wenzhong (Jixie chuandong)
According to the structure and motion characteristics of the split-power internal parallel moving gear transmission device,the transmission efficiency is studied,and the mathematical model of the transmission efficiency of the split-power internal parallel moving gear transmission device（SIPMGTD） is obtained. Taking the internal parallel moving gear pair（IPMGP） with 2 teeth difference as an example,the meshing efficiency is analyzed.When the transmission ratio is less than 100,the meshing efficiency can reach 96. 7% 98. 2%. The efficiency test bench of the SIPMGTD prototype is set up,the real-time efficiency monitoring software of the experiment platform is compiled,and the real-time monitoring system of efficiency is constructed. The test results show that the test results are in good agreement with the theoretical analysis results. The mathematical model of efficiency is accurate and believable. The SIPMGTD with large transmission ratio has high transmission efficiency.